METODE MENDIDIK ANAK DALAM PANDANGAN ISLAM - Siregar, Fitri Rayani (FORUM PAEDAGOGIK, 2016)
A method has important rule  in educating the children for reaching a goal of education that is hoped by parents. Because of that, the parents must have knowledge and education for choosing the method, the  children grow up in bad condition  if they choice the wrong method.  Based on view of Islam there are some methods in raising children in Islamic, thay are: modelling method, love method, advice method, communication method, action method, telling story method, reward and punishment method and playing method. Modelling method is a parents as modelling especially in religious aspect. Love method  is a method  that use by loving. In advice method a parents can be using the Alqur’an and Sunnah for teaching them. Telling story method is a method when a parents must like telling a good story for building their character. Reward and punishment methods are methods that can be combined and this case the parents must be wise. And the last is playing method, this method brings the parents in comportable gratifying condition. The childreen will be happy and smart. Finally,  The parents can be able to use all the method above based on the condition of their children, which one is compatible for them. Alqur’an and Sunnah Rasululluh Saw support to all the methods.  So there is no doubt for choosing all the methods.